Lebur Alako Ka’ Tasek: Navigating Resilience of Pasongsongan Fisher Community in Madura (Universitas Terbuka, 2025)
Climate change that has hit the entire Minapolitan area is so worrying, it is not only a threat to the Blue Economy order in Indonesia, but also to the entire fishing community. The people of Pasongsongan Village Madura are one of the coastal communities which quite vulnerable to climate change. Data from the Sumenep Fisheries Office (local government) stated that production achievements in 2023-2024 were somewhat reduced due to bad weather even though this sub-district received appropriate technological aids and also the System Information Kapal which is cutting-edge application form the goverment. This research successfully explores the vulnerability of coastal communities in the midst of climate change and how they collaborate with governments and institutional agencies through various strategies. This study used the Theory of Practice from Pierre Bourdieu in the concept of Habitus and capital with a phenomenological approach. The data collection technique used In-depth interview, observation and focus group discussion with the source triangulation analysis technique. The results of this study revealed several findings, first, institutional agencies that are established in collaboration between fishermen and the Sumenep Regency government both in the context of bonding social capital, Bridging Social Capital, and Linking Social capital are part of participatory decision making in saving the Madura Strait area. Second, the spirit of